Worksite tracing in Archaeological Architecture. A reconstruction workflow - Alfonso Ippolito; Martina Attenni; Carlo Bianchini; Carlo Inglese; Marika Griffo (Disegnare con, 2017)
The process of designing an architectural project has always been among the most explored fields of research. On the one hand, it proves to be a historical document of cultural heritage; on the other hand, however, it allows the researcher to grasp the relations obtaining between the design idea and its realization. In this frame of reference the present study of worksite tracings is focused on detail designing. The study of these signs con- ducted by integrating the traditional surveying techniques with the technologies of massive ac-quisition as well as with the digital methodolo-gies of model constructing has been carried out in order to grasp the relations between the idea and its realization by continuously comparing real and ideal models, thus extending the knowledge and the documentation of ancient artifacts.